A spatio-temporal probability model of cattle and African buffalo (Syncerus caffer) contact as a proxy for foot-and-mouth disease risk : a case study at the wildlife-livestock interface of the Kruger National Park, South Africa - Knobel, Darryn Leslie (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2015.